ADHD Symptoms in Preschool Children: Examining Psychometric Properties using IRT - Purpura, David J. (2010)
Clear and empirically supported diagnostic symptoms are important for proper diagnosis and treatment of psychological disorders. Unfortunately, symptoms of many disorders presented in the DSM-IV-TR lack sufficient psychometric evaluation. In this study, an Item Response Theory analysis was applied to ratings of the 18 Attention-Deficit/Hyperactivity Disorder (ADHD) symptoms in 268 preschool children. Children (55% boys) in this sample ranged in age from 37 to 74 months; 80.4% were identified as African American, 15.1% Caucasian, and 4.5% other ethnicity. Dichotomous and polytomous scoring methods for rating ADHD symptoms were compared and psychometric properties of these symptoms were calculated. Symptom-level analyses revealed that, in general, the current symptoms provided useful information in diagnosing ADHD in preschool children; however, several symptoms provided redundant information and should be examined further.